Dried blood spots: An evaluation of utility in the field. Issue 3 (May 2018) - Su, Xu; Carlson, Bradley F.; Wang, Xiexiu; Li, Xiaoyan; Zhang, Ying; Montgomery, JoLynn P.; Ding, Yaxing; Wagner, Abram L.; Gillespie, Brenda; Boulton, Matthew L.
Abstract: Background: Use of dried blood spots (DBS) offers advantages over serum samples in studies conducted in resource-poor settings. The aim of this study was to compare the number of adequate spots collected across different demographic groups. Methods: Five DBS were collected from 3316 individuals aged 0–49 years in Tianjin, China for a measles antibody study; DBS were rated "adequate" or "inadequate." Linear regression, with the number of adequate DBS on a card as the outcome variable, was used to test for predictors of DBS adequacy. Results: There were 0 adequate DBS for 23% of participants and 5 adequate DBS for 24%. Mean number of adequate DBS was 1.68 in infants (<12 months), 2.57 (1–9 years), 3.49 (10–29 years), 3.08 (30–49 years). The number of adequate DBS increased over the study; the mean number of adequate DBS for the five years 2011–2015 were 1.21, 2.52, 3.40, 2.22, and 3.62, respectively. DBS quality was not related to measles IgG antibodies. Conclusions: DBS are an alternative for adults and children but pose challenges in infants, and improve with experience. In a resource-limited environment or in a scenario where more invasive techniques like venipuncture may be less accepted by the study population, DBS can be the preferred technique to efficiently obtain serum specimens for analyte testing.